2019
DOI: 10.3390/medicina55050151
|View full text |Cite
|
Sign up to set email alerts
|

Manual Massage Therapy for Patients with COPD: A Scoping Review

Abstract: Background and objectives: Manual massage therapy is a therapeutic option for the treatment of several pathological conditions affecting the musculoskeletal system. It has been pointed out that massage might be beneficial for chronic obstructive pulmonary disease (COPD) patients thanks to therapeutic effects primarily related to hyperemia (increased skin temperature and blood flow), and activation of the lymphatic system. The present study reports current evidence on the systemic effects of manual massage in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
3
1
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 25 publications
0
3
1
1
Order By: Relevance
“…A similar study has not been performed on the effect of massage therapy on respiratory volume, but according to the results of this study, the study of Sharifizari et al (2017) showed that massage of LI4 and HT7 points in cancer patients undergoing bone marrow biopsy had a significant reduction in pain but had no effect on patients' respiration and blood pressure [ 16 ]. However, contrary to the results of this study, Polastri et al (2019) showed that manual massage in chronic obstructive pulmonary disease (COPD) improves active expiratory volume and relieves shortness of breath [ 28 ]. Also in the study of Nekooee et al (2008), there was a significant difference in the mean of spirometric indices (forced vital capacity (FVC) and forced expiratory volume (FEV) in the massage group at the beginning and after one month of follow-up, and researchers report that daily massage can improve airway strength, reduce airway sensitivity, and improve asthma control, therefore, the use of this method can reduce the use of irrational drugs and can be considered as a complementary method to pharmacological methods [ 29 ].…”
Section: Discussioncontrasting
confidence: 77%
“…A similar study has not been performed on the effect of massage therapy on respiratory volume, but according to the results of this study, the study of Sharifizari et al (2017) showed that massage of LI4 and HT7 points in cancer patients undergoing bone marrow biopsy had a significant reduction in pain but had no effect on patients' respiration and blood pressure [ 16 ]. However, contrary to the results of this study, Polastri et al (2019) showed that manual massage in chronic obstructive pulmonary disease (COPD) improves active expiratory volume and relieves shortness of breath [ 28 ]. Also in the study of Nekooee et al (2008), there was a significant difference in the mean of spirometric indices (forced vital capacity (FVC) and forced expiratory volume (FEV) in the massage group at the beginning and after one month of follow-up, and researchers report that daily massage can improve airway strength, reduce airway sensitivity, and improve asthma control, therefore, the use of this method can reduce the use of irrational drugs and can be considered as a complementary method to pharmacological methods [ 29 ].…”
Section: Discussioncontrasting
confidence: 77%
“…Physical exercise, as the primary intervention, includes active exercises such as walking and stair exercises. Some researchers recommend Manual therapy (MT) as an additional treatment option in association with other interventions, such as physical exercise [ 18 ], and MT that targets the respiratory muscles would be particularly beneficial for patients with COPD to develop muscle strength and maintain muscle movement [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…The consequent pulmonary hyperinflammation or increased respiratory demand causes breathing distress, a change in breathing patterns, or a fall in motor ability. As a result, COPD patients experience limited and reduced physical activity, which may cause skeletal muscle wasting, sarcopenia, or cachexia [4] . In recent studies, therefore, emphasis has been placed on nonpharmacological therapy, including respiration rehabilitation, for managing the underlying symptoms of COPD [1] .…”
Section: Introductionmentioning
confidence: 99%
“…As a result, COPD patients experience limited and reduced physical activity, which may cause skeletal muscle wasting, sarcopenia, or cachexia. [ 4 ] In recent studies, therefore, emphasis has been placed on nonpharmacological therapy, including respiration rehabilitation, for managing the underlying symptoms of COPD. [ 1 ] In respiration rehabilitation, the main focus has been on exercise therapy, and recently, MT has received much attention.…”
Section: Introductionmentioning
confidence: 99%